2004
DOI: 10.1210/jc.2003-031183
|View full text |Cite
|
Sign up to set email alerts
|

Change in Estradiol and Follicle-Stimulating Hormone across the Early Menopausal Transition: Effects of Ethnicity and Age

Abstract: Serum reproductive hormone concentrations were measured longitudinally in a community-based, multiethnic population of midlife women to assess whether ethnic differences exist in the patterns of change in estradiol (E2) and FSH and, if so, whether these differences are explained by host characteristics. We studied 3257 participants from seven clinical sites in the Study of Women's Health Across the Nation (SWAN) who were aged 42-52 yr at baseline and self-identified as African American (28.2%), Caucasian (47.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
182
3
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(207 citation statements)
references
References 32 publications
14
182
3
5
Order By: Relevance
“…Serum estradiol levels were also lower in the same age group, but LH levels did not vary significantly in any of the age groups. Recent largescale cohort studies conducted in Australia [235][236][237][238], Norway [239], and United States [240] have provided further important insights into the overall pattern of ovarian sex steroids and gonadotropins that occur during the MT. It is reported that circulating FSH levels rise progressively during the MT and that in perimenopausal women estradiol production fluctuates with FSH and often reaches higher concentrations than those in young normal cycling women below the age of 35.…”
Section: Aging and Secretion Of Female Sex-steroidsmentioning
confidence: 99%
“…Serum estradiol levels were also lower in the same age group, but LH levels did not vary significantly in any of the age groups. Recent largescale cohort studies conducted in Australia [235][236][237][238], Norway [239], and United States [240] have provided further important insights into the overall pattern of ovarian sex steroids and gonadotropins that occur during the MT. It is reported that circulating FSH levels rise progressively during the MT and that in perimenopausal women estradiol production fluctuates with FSH and often reaches higher concentrations than those in young normal cycling women below the age of 35.…”
Section: Aging and Secretion Of Female Sex-steroidsmentioning
confidence: 99%
“…Recent data show that Asian women in the United States undergoing menopause have lower estradiol levels than Caucasian women (33,34). Adipose tissue is a major source of estradiol in postmenopausal women, and the higher estradiol levels in Caucasians may be due, in part, to the greater adiposity of Caucasian women (32,33).…”
Section: Natural Menopause Estrogen Replacement Therapy and Arthralgiamentioning
confidence: 99%
“…Adipose tissue is a major source of estradiol in postmenopausal women, and the higher estradiol levels in Caucasians may be due, in part, to the greater adiposity of Caucasian women (32,33).…”
Section: Natural Menopause Estrogen Replacement Therapy and Arthralgiamentioning
confidence: 99%
“…1a). During this early phase up to 5 years before the last menstrual period, estrogen levels are relatively unperturbed, whereas follicle-stimulating hormone (FSH) levels are rising to compensate for failing ovaries [6,7] (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…1 Bone loss at the most rapid rate in obese (top panel) or non-obese (bottom panel) begins 2-3 years before the last menstrual period (a), during which time serum estrogen levels are stable while serum FSH is rising (b). Adapted, with permission, from refs [3] and [6] more closely using appropriate primers [26]. Furthermore, injection of FSH into mice with intact ovaries [34], or its transgenic overexpression [33], even in hpg mice, is unlikely to reveal pro-resorptive actions of FSH.…”
Section: Introductionmentioning
confidence: 99%